Development Of History Learning Module Based On Religious Values At State High School 1 Palembang - Asani Yunia Rokhman; LR Retno Susanti; Hudaidah Hudaidah (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2018)
Education is one of the manifestations of the implementation of the objectives of the Republic of Indonesia contained in the 4th paragraph of the 1945 Constitution which reads